2019
DOI: 10.3390/ijms20184621
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone Treatment after Transient Ischemia Induces Hypothermia and Provides Neuroprotection in the Gerbil Hippocampus by Decreasing Oxidative Stress

Abstract: Compelling evidence from preclinical and clinical studies has shown that mild hypothermia is neuroprotective against ischemic stroke. We investigated the neuroprotective effect of post-risperidone (RIS) treatment against transient ischemic injury and its mechanisms in the gerbil brain. Transient ischemia (TI) was induced in the telencephalon by bilateral common carotid artery occlusion (BCCAO) for 5 min under normothermic condition (37 ± 0.2 °C). Treatment of RIS induced hypothermia until 12 h after TI in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…Finally, we investigated CD200 immunoreactivity in the ischemic CA1 field after postischemic treatment with 10 mg/kg RIS, because we recently demonstrated that therapeutic treatment with 10 mg/kg RIS after 5-min tFI in gerbils displayed excellent neuroprotective effects in a gerbil model of tFI and a rat model of MCAO-induced transient focal cerebral ischemia [ 36 , 37 ]. We found that posttreatment with RIS strongly protected pyramidal neurons in the ischemic CA1 field: this finding is consistent with the previous finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we investigated CD200 immunoreactivity in the ischemic CA1 field after postischemic treatment with 10 mg/kg RIS, because we recently demonstrated that therapeutic treatment with 10 mg/kg RIS after 5-min tFI in gerbils displayed excellent neuroprotective effects in a gerbil model of tFI and a rat model of MCAO-induced transient focal cerebral ischemia [ 36 , 37 ]. We found that posttreatment with RIS strongly protected pyramidal neurons in the ischemic CA1 field: this finding is consistent with the previous finding.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether CD200 affected the neuroprotection of the CA1 pyramidal neurons from tFI injury, 10 mg/kg RIS was treated after tFI according to a published method [36]. It was reported that treatment with RIS, an atypical antipsychotic drug, after tFI induced hypothermia and provided neuroprotection in the gerbil hippocampal CA1 field by decreasing oxidative stress (Yang et al, 2019).…”
Section: Posttreatment With Rismentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, vehicle or RIS (10 mg/kg) (Sigma-Aldrich, St. Louis, MO, USA) was injected into the peritoneal cavity immediately after ACA/CPR operation. The dose of RIS was selected based on a previous study [21]. RIS was dissolved in 0.3% Tween 80 (in 0.85% saline; NaCl w/v; Junsei Chemical Co., Ltd., Tokyo, Japan).…”
Section: Aca/cpr Operation and Ris Treatmentmentioning
confidence: 99%
“…Studies in 2003 and 2004 reported that RIS induced hypothermia in patients with brain disorders, such as schizophrenia [19,20]. In a recent experimental study, RIS induced hypothermia in gerbils and effectively protected cells or neurons from ischemiareperfusion injury in the hippocampus by attenuating glial activation and maintaining antioxidants [21].…”
Section: Introductionmentioning
confidence: 99%